PENGARUH PEMANFAATAN JERUK NIPIS TERHADAP PENYEMBUHAN KETOMBE KERING DI KULIT KEPALA - Rahmadani, Rahmadani; Hayatunnufus, Hayatunnufus; Yuliana, Yuliana (Journal of Home Economics and Tourism, 2012)
This study aims to analyze the use of dry dandruff cure lime assessed from theskin itching of the head, the amount of crust / dandruff, scalp conditions and hair losslevels with 3 levels of the control group treated without the use of lime, experimentalgroup 1 with one time a day treatment and experimental group 2 with treatment one timein 2 days. This type of quasi experimental study. Sampling was purposive samplingtechnique was used by volunteers. The sample was 9 student UNP who wear veils andindicated suffering from dry dandruff. Data analysis was descriptive and analyticalVarian. The results showed that the cure dandruff in the control group did not show achange towards the better on every indicator while the experimental group one andexperiment there is a significant effect on each indicator. The difference between thehealing effect of three treatment groups showed significant results on each indicator. Useof lemon juice can cure dandruff considerably with the best use of the frequency in thetreatment group once a day.